Neutrophil-specific deletion of the CARD9 gene expression regulator suppresses autoantibody-induced inflammation in vivo - Németh, Tamás (Nat Commun, 2016)
Neutrophils are terminally differentiated cells with limited transcriptional activity. The biological function of their gene expression changes is poorly understood. CARD9 regulates transcription during antifungal immunity but its role in sterile inflammation is unclear. Here we show that neutrophil CARD9 mediates pro-inflammatory chemokine/cytokine but not lipid mediator release during non-infectious inflammation. Genetic deficiency of CARD9 suppresses autoantibody-induced arthritis and dermatitis in mice. Neutrophil-specific deletion of CARD9 is sufficient to induce that phenotype. Card9(−/−) neutrophils show defective immune complex-induced gene expression changes and pro-inflammatory chemokine/cytokine release but normal LTB(4) production and other short-term responses. In vivo deletion of CARD9 reduces tissue levels of pro-inflammatory chemokines and cytokines but not LTB(4). The CARD9-mediated signalling pathway involves Src-family kinases, Syk, PLCγ2, Bcl10/Malt1 and NFκB. Collectively, CARD9-mediated gene expression changes within neutrophils play important roles during non-infectious inflammation in vivo and CARD9 acts as a divergence point between chemokine/cytokine and lipid mediator release.